Intraradical dynamics of two coexisting isolates of the arbuscular mycorrhizal fungus Glomus intraradices sensu lato as estimated by real-time PCR of mitochondrial DNA - Krak, Karol; Janoušková, Martina; Caklová, Petra; Vosátka, Miroslav; Štorchová, Helena (Applied and environmental microbiology, 2012)
Real-time PCR in nuclear ribosomal DNA (nrDNA) is becoming a well-established tool for the quantification of arbuscular mycorrhizal (AM) fungi, but this genomic region does not allow the specific amplification of closely related genotypes. The large subunit of mitochondrial DNA (mtDNA) has a higher-resolution power, but mtDNA-based quantification has not been previously explored in AM fungi. We applied real-time PCR assays targeting the large subunit of mtDNA to monitor the DNA dynamics of two isolates of Glomus intraradices sensu lato coexisting in the roots of medic (Medicago sativa). The mtDNA-based quantification was compared to quantification in nrDNA. The ratio of copy numbers determined by the nrDNA- and mtDNA-based assays consistently differed between the two isolates. Within an isolate, copy numbers of the nuclear and the mitochondrial genes were closely correlated. The two quantification approaches revealed similar trends in the dynamics of both isolates, depending on whether they were inoculated alone or together. After 12 weeks of cultivation, competition between the two isolates was observed as a decrease in the mtDNA copy numbers of one of them. The coexistence of two closely related isolates, which cannot be discriminated by nrDNA-based assays, was thus identified as a factor influencing the dynamics of AM fungal DNA in roots. Taken together, the results of this study show that real-time PCR assays targeted to the large subunit of mtDNA may become useful tools for the study of coexisting AM fungi.
Keywords: DNA fungální; Medicago sativa; Microbial Interactions; molekulární sekvence - údaje; DNA, Fungal; Real-Time Polymerase Chain Reaction; mikrobiální interakce; DNA, Mitochondrial; sekvenční analýza DNA; Sequence Analysis, DNA; Plant Roots; kořeny rostlin; kvantitativní polymerázová řetězová reakce; Colony Count, Microbial; mitochondriální DNA; počet mikrobiálních kolonií; Glomeromycota; Molecular Sequence Data